Tiger's Curse - Book 1 - Houck, Colleen (New York, 2011)
When Kelsey forms a bond with a circus tiger who is actually one of two brothers, Indian princes Ren and Kishan, who were cursed to live as tigers for eternity, she travels with him to India where the tiger's curse may be broken once and for all.
Map on lining papers.
Keywords: Circus; Fiction; Orphans; Tigers; Fiction; Immortality; Fiction; Fiction; Fiction; India